AMBIENT PM2.5 CONCENTRATION AND THE RISK OF HYPERTENSION IN ADULTS: A META-ANALYSIS STUDY - Achmad Rizki Azhari; Maya Sari; Osep Yasier Almunsiri; Nur Afifah Harahap (Proceeding of Banten Internasional Conference on Health Advancement and Research, 2026)
Long-term exposure to ambient fine particulate pollution (PM2.5) has been associated with cardiovascular diseases. Hypertension, a major risk factor for cardiovascular diseases, has also been hypothesized to be linked to PM2.5. Annual average PM2.5 concentrations were estimated for each community using satellite data. We applied two-level logistic regression models to examine the associations, and estimated hypertension burden attributable to ambient PM2.5.